Analysis of the Effect of District / City Minimum Wage and Labor Force Participation Rate on the Open Unemployment Rate of North Sumatra Province in 2021-2022 - Erwin; Hasibuan, Citra Dewi; Marpaung, Rony Genevent; Marpaung, J.L. (Journal of Mathematics Technology and Education, 2023)
Open unemployment is still a major economic problem in North Sumatra Province. This study aims to analyze the effect of Regency / City Minimum Wage, Labor Force Participation Rate, and Gross Regional Domestic Product on the Open Unemployment Rate in North Sumatra Province in 2021-2022. The type of data used is secondary data obtained from the North Sumatra Province Statistics Agency. The results showed that there was a simultaneous significant influence between the three independent variables, namely district / city minimum wage, labor force participation rate, and gross regional domestic product on the dependent variable, namely the open unemployment rate ???? = 0.164????1 − 0.694????2 − 0.032???? + 0.424. The simultaneous effect is 57.6% and the remaining 42.4% is explained by other variables not included in the study.